Effect of idebenone supplementation in a semen extender on boar spermatozoa quality during liquid storage - Rehardus Ricco Pantecostoma; Jatesada Jiwakanon; Saksiri Sirisathien (Veterinary World)
Background and Aim: In swine production, over 99% of artificial insemination (AI) procedures utilize boar semen preserved in liquid form at 17°C for up to 5 days. However, spermatozoa are highly susceptible to oxidative stress during storage, which impairs motility, membrane integrity, and overall fertility. Reactive oxygen species-induced lipid peroxidation (LPO) compromises sperm structure and function. Although antioxidants are used to mitigate oxidative damage, idebenone (IDB) – a short-chain benzoquinone with potent mitochondrial antioxidant properties – has not been studied in boar semen preservation. This study aimed to investigate the effects of IDB supplementation in a semen extender on boar spermatozoa quality during 120 h of liquid storage at 17°C.